The Effectiveness of Student Teams-Achievement Divisions in Enhancing Visual and Auditory for English Students’ Writing Skill - Nisa, Baiatun; Sari, Sulhizah Wulan (Bina Nusantara University, 2019)
This research discussed the effectiveness of learning English writing using the Student Teams-Achievement Divisions (STAD) and lecture-based learning method. The two methods were applied in two classes of second-year students, and they were given a writing test over one semester. The first class was using STAD and the second class with lecture-based learning. Around 80 students were classified into visual and auditory learning styles based on the questionnaires filled in. The results in the statistical analysis provide important insights into the learning achievement of both visual and auditory learners modeled by STAD. Using the STAD method, they have accomplished considerably higher scores on academic writing achievement than the students who are taught by lecture-based learning. Therefore, it brings a positive effect and association with the students’ learning styles.